Principles of Microeconomics - Gregory, Mankiw, N.
Mankiw's Principles of Economics textbooks continue to be the most popular and widely used text in the economics classroom. PRINCIPLES OF MICROECONOMICS, 4th Edition features a strong revision of content in all 22 chapters while maintaining the clear and accessible writing style that is the hallmark of the highly respected author. The 4th edition also features an expanded instructor's resource package designed to assist instructors in course planning and classroom presentation and full integration of content with Aplia, the leading online Economics education program. In the 4th edition Greg Mankiw has created a full educational program for students and instructors -- Experience Mankiw 4th edition